Designing Problem-Based Learning Through Narrative Stories for Microteaching Class Using Addie Model - Anita Galuh Sri Hapsari; Paulus Kuswandono (JEELS (Journal of English Education and Linguistics Studies), 2020)
This research aimed to design a reflection book as a set of problem-based learning (PBL) for a supplementary material in Microteaching class. The book was developed not only to assist pre-service English teachers (PSETs) undergoing Microteaching class to understand real problems in school context, but also to help them enhance their problem-solving skill through critical reflection and discussion. This book was designed by implementing ADDIE model, consisting of five phases, namely Analysis, Design, Development, Implementation, and Evaluation. This product was formatively evaluated within the Analysis, Design, Development and Implementation phases and was field tested in Microteaching class comprising of 19 PSETs from the English Language Education Study Program in Tuladha University (pseudonym). In the last stage, summative evaluation was conducted by two subject matter experts whose background was both English education lecturers and book authors. Product validation included narrative story aspect and reflective activities. The validation result showed that the book was appropriate and practical for enhancing PSETs’ problem-solving skill.